Ten x 100 swim test protocol: A simple & effective test for swimmers of all ages - Goldsmith, W. (coachesinfo.com, 2001)
The 10x100-m-test described here is a simple but effective and useful swimming test set that coaches and competitive swimmers of all ages can use to measure where they are in their preparation. It is a MULTI DISCIPLINARY test protocol which means it looks at physiological areas as well as biomechanical and technical aspects of swimming performance.